Geriatric trauma prognosis trends over 10 years: analysis of a nationwide trauma registry - Hiromichi Naito; Atsunori Nakao; Takeshi Nishimura; Shinichi Nakayama (Trauma Surgery & Acute Care Open)
Purpose With Japan’s population rapidly skewing toward aging, the number of geriatric trauma patients is expected to increase. Since we need to continue to improve the quality of geriatric trauma patient care, this study aimed to evaluate in-hospital mortality trends among geriatric trauma patients in Japan over a recent 10-year period.Methods This was a retrospective cohort study of data from a Japanese nationwide trauma registry (the Japan National Trauma Data Bank) on patients admitted between January 1, 2008 and December 31, 2017. Geriatric patients were defined as those 65 years old and older. The primary outcome was to clarify in-hospital mortality trends and changes over these 10 years.Results We identified 265 268 eligible trauma patients. Excluding those under 65 years old and those with inadequate or unknown age data, missing prognosis, out-of-hospital cardiac arrest, and burns, 107 766 patients were enrolled in this study. The total trauma patient in-hospital mortality trend was evaluated using the Cochran-Armitage test and showed a significant decrease (p<0.001). Although severe trauma patients (Injury Severity Score (ISS) ≥16) showed a significant decreasing trend (p<0.001) over time (from 26.1% to 14.5%), less-severe trauma patients (ISS <16) did not (p=0.41) (from 2.7% to 2.1%). Mixed logistic regression analysis showed that the number of year patients stayed in the hospital was significantly associated with mortality.Conclusions While recognizing the limitations of the current analysis, our data demonstrated that prognoses for severe trauma patients over 65 years old improved dramatically over these 10 years, especially in those with severe trauma.Level of evidence Ⅲ—retrospective cohort study.